Application Of Problem Based Learning Model To Improve Negotiation Text Writing Skills In Class X AKL 1 SMK Negeri 1 Duduksampeyan - Wangi, Nisaul Barokati Seliro; Pradana, Mohammad Syaiful; Saifuddin, Saifuddin (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
In learning Indonesian in class X SMA/SMK/MA, there are activities to write negotiating texts. According to the results of observations made by researchers, the ability to write negotiating texts for class X students at SMK Negeri 1 Duduksampeyan is still relatively low. Thus, it is necessary to apply a learning model, namely a problem-based learning model to overcome these problems. This study aims to (1) improve negotiating text writing skills, (2) describe student activities, (3) describe teacher activities, and (4) describe student responses. This research is qualitative by using Classroom Action Research (CAR). The subjects of this study were students of class X AKL 1 SMKN 1 Duduksampeyan. The research instruments were learning outcomes tests, observation sheets, and student questionnaires. Collecting data with test results, student observation sheets, and student response questionnaire sheets. The technique used is the descriptive qualitative data analysis technique. Based on the results of the study, it is known that the increase in learning outcomes of negotiating texts obtained from the first cycle obtained an average score of 78.78% until the second cycle became 82.15%.   Keywords: problem-based learning, writing skills, negotiating text, teacher activities, student activities.